Projekt Slovensko javno mnenje in njegov čas SJM 1968-1999 - Toš, Niko (Družboslovne razprave, 1999)
In the first part of the article the author outlines the design and development of Slovenian Public Opinion project (Slovensko javno mnenje - SJM) between 1968-1999. The SJM project is the leading national social survey project and empirical 'infrastructure' of Slovenian social sciences. It has developed simultaneously with similar projects in North American and Western European countries (General Social Survey, Allbus). Using longitudinal data from SJM survey, the author outlines general value patterns in Slovenian public, concerning various social, economic and political issues. He focuses on transition of values in the period of political transition, that bears significant importance for Slovenian nation (period of self determination). The paper may be considered a contribution for a history of Slovenian sociology. It contributes to deeper understanding of value changes in Slovenian public in the period of transition from authoritarian regime to democratic political system.
Keywords: Slovenia; Slovenija; javno mnenje; 1968/1999